2000
DOI: 10.1177/002215540004800308
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Prolactin mRNA in Rat Mammary Gland During Pregnancy and Lactation

Abstract: We studied the expression of prolactin (PRL) mRNA in the mammary gland of resting, pregnant, lactating, and weanling rats using in situ and solution reverse transcriptase-polymerase chain reaction (RT-PCR). In mid- to late pregnancy and throughout lactation, PRL mRNA was detected in both in situ and solution RT-PCR. These PRL mRNA signals were clearly identified in the cytoplasm of alveolar and ductal mammary epithelial cells by the in situ RT-PCR method. In mid- to late pregnancy, such as at the initiating po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2001
2001
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…Autocrine prolactin mRNA expression in the mammary gland has been detected in late-pregnant and lactating rats (Kurtz et al 1993;Steinmetz et al 1993;Iwasaka et al 2000;Ben-Jonathan et al 2008). In this regard, the sole report of a function for autocrine prolactin in a normal tissue arises from studies comparing proliferation rates in recombined mouse mammary glands composed of either Prl À/À or Prl +/+ epithelium transplanted into wild-type mammary stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Autocrine prolactin mRNA expression in the mammary gland has been detected in late-pregnant and lactating rats (Kurtz et al 1993;Steinmetz et al 1993;Iwasaka et al 2000;Ben-Jonathan et al 2008). In this regard, the sole report of a function for autocrine prolactin in a normal tissue arises from studies comparing proliferation rates in recombined mouse mammary glands composed of either Prl À/À or Prl +/+ epithelium transplanted into wild-type mammary stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Studies utilizing bromocriptine, which inhibits pituitary PRL synthesis, or pituitary isographs, which secrete large amounts of PRL, have established that endocrine PRL is largely responsible for PRL's reported physiological functions (Freeman et al, 2000). However, PRL is also synthesized in several extrapituitary sites, including mammary epithelial cells (Lkhider et al, 1996;Escalada et al, 1997;Iwasaka et al, 2000), raising the possibility that in addition to PRL's demonstrated direct and indirect endocrine roles, it may regulate mammopoiesis via an autocrine or paracrine mechanism. We addressed this question by comparing the development of transplanted mammary epithelium with and without a null mutation of the PRL gene, using the endpoints of morphology/histology, cell proliferation, and cell apoptosis.…”
Section: Mammary Prl Production Is Not Required For Normal Developmentioning
confidence: 99%
“…Interestingly, PRL appears to not be expressed in the rat liver (Kurtz et al 1993), a tissue rich in PRLR (Bole-Feysot et al 1998). In rats, PRL mRNA is first expressed within the mammary gland at midlate pregnancy and is expressed throughout lactation (Iwasaka et al 2000). Along these lines, precocious lactogenesis in neonatally-estrogenized nulliparous female mice coincides with elevated expression of PRL mRNA in the mammary gland (Hovey et al 2005).…”
Section: Introductionmentioning
confidence: 99%